Constituent structure in a tagalog text - LaPolla, Randy J. (2014)
If there are no classes of noun or verb in Tagalog, how can there be noun phrases and verb phrases? This paper contributes to the discussion on form classes in Tagalog by taking a detailed, inductive, line-by-line look at the structures and constituents found in a randomly selected Tagalog text, to create a typology of the structures found therein. It is shown that, while there are very obvious constructions with generally clearly differentiated functions, they do not correspond with noun phrases and verb phrases in Indo-European languages, as it cannot be said that one form is used for predication and another for reference.